Isoquinoline Alkaloids from Fumaria officinalis L. and Their Biological Activities Related to Alzheimer's Disease - Chlebek, Jakub; Novák, Zdeněk; Kassemová, Dominika; Šafratová, Marcela; Kostelník, Jan; Malý, Lukáš; Ločárek, Miroslav; Opletal, Lubomír; Hošt'álková, Anna; Hrabinová, Martina; Kuneš, Jiří; Novotná, Pavlína; et al. (Chemistry & biodiversity, 2016)
Two new isoquinoline alkaloids, named fumaranine (2) and fumarostrejdine (10), along with 18 known alkaloids were isolated from aerial parts of Fumaria officinalis. The structures of the isolated compounds were elucidated on the basis of spectroscopic analyses and by comparison with literature data. The absolute configuration of the new compound 2 was determined by comparing its circular dichroism spectra with those of known analogs. Compounds isolated in sufficient amounts were evaluated for their acetylcholinesterase, butyrylcholinesterase, prolyl oligopeptidase (POP), and glycogen synthase kinase-3β inhibitory activities. Parfumidine (8) and sinactine (15) exhibited potent POP inhibition activities (IC50 99±5 and 53±2 μM, resp.).
Keywords: prolyloligopeptidasy; Glycogen synthase kinase-3β; Prolyl Oligopeptidases; Structure-Activity Relationship; Alkaloids; molekulární struktura; Molecular Structure; Fumaria; vztah mezi dávkou a účinkem léčiva; Alzheimerova nemoc; Alzheimer Disease; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Enzyme Inhibitors; Isoquinoline alkaloids; Fumaria officinalis; acetylcholinesterasa; vztahy mezi strukturou a aktivitou; alkaloidy; lidé; Serine Endopeptidases; isochinoliny; Humans; Butyrylcholinesterase; kinasa 3 glykogensynthasy; serinové endopeptidasy; Isoquinolines; Prolyl oligopeptidase; butyrylcholinesterasa; Acetylcholinesterase; Dose-Response Relationship, Drug; inhibitory enzymů; kinasa glykogensynthasy 3beta